Impact of education in patients undergoing physiotherapy for lower back pain: a level I systematic review and meta-analysis - Migliorini, Filippo; Maffulli, Nicola; Schäfer, Luise; Manocchio, Nicola; Bossa, Michela; Foti, Calogero; Betsch, Marcel; Kubach, Joshua (European Journal of Trauma and Emergency Surgery, 2025)
Introduction: Lower back pain (LBP) is one of the most common musculoskeletal disorders in modern society, with a lifetime incidence of up to 90%. According to most national and international guidelines, educational interventions play a central role in the multimodal treatment of LBP. This systematic review and meta-analysis investigated the impact of educational interventions on pain and disability in patients with LBP undergoing physiotherapy compared to patients without educational interventions undergoing physiotherapy. Methods: In October 2024, a comprehensive computer-aided search was performed to assess the online databases PubMed, Web of Science, Google Scholar, and Embase. The search followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) criteria with an established PICOTD algorithm. Two authors independently performed the data extraction and risk of bias evaluation. The primary outcome measures extracted were a pain score (VAS or NRS) and the Roland Morris Disability Questionnaire (RMQ). Results: Data from 8152 patients were retrieved. The mean length of follow-up was 6.2 ± 3.9 months, the mean length of symptom duration was 66.7 ± 51.6 months, and the mean age of the patients was 46.7 ± 9.2 years. Compared to physiotherapy alone, additional education did not reduce pain (P = 0.4) or disability according to the RMQ (P = 0.9). Conclusion: The addition of education did not impact pain and disability in patients undergoing physiotherapy for chronic non-specific LPB. Level of evidence: Level I, systematic review and meta-analysis of RCTs.
CRIS-Team Scopus Importer:2025-03-14
Keywords: Education; Lower back pain; Physiotherapy; Spine